2016
DOI: 10.1136/bmjopen-2016-011947
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism and mortality following total ankle replacement: a data linkage study using the NJR data set

Abstract: ObjectiveTo determine the mortality rate following total ankle replacement (TAR) and incidence of 90 day pulmonary embolism (PE) along with the associated risk factors.DesignData-linkage study of the UK National Joint Registry (NJR) data and Hospital Episodes Statistics (HES) database. Linkage was performed in a deterministic fashion. HES episodes 90 days after the index procedure were analysed for PE. Mortality data were obtained pertaining to all the index procedures from the NJR for analysis.ParticipantsAll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Whether vessel wall embolization or in-situ inclusion of vessel wall components into the thrombus is a common phenomenon in MT remains unclear. This patient suffered from ischemic stroke soon after orthopedic surgery but as the incidence of pulmonary embolism after such operations are low ( 37 ) there may be no causality in this case but a mere coincidence.…”
Section: Discussionmentioning
confidence: 88%
“…Whether vessel wall embolization or in-situ inclusion of vessel wall components into the thrombus is a common phenomenon in MT remains unclear. This patient suffered from ischemic stroke soon after orthopedic surgery but as the incidence of pulmonary embolism after such operations are low ( 37 ) there may be no causality in this case but a mere coincidence.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, 9 studies with a total of 10 388 patients were eligible for inclusion in the quantitative analysis [6][7][8]15,16,26,53,62,64 and 28 in the narrative synthesis. [1][2][3][4][5][9][10][11]13,14,[17][18][19]23,25,29,[34][35][36]40,44,47,48,50,51,56,59,65…”
Section: Search and Selectionmentioning
confidence: 99%
“…7,8,16 Such complications may predispose to revision, explant, or even amputation following the initial ankle replacement. 37 Current data on revision rates following TAR is mixed. A Medicare study by Tucker et al 32 reported the 9-year revision rate of TAR at 11%.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 16 Such complications may predispose to revision, explant, or even amputation following the initial ankle replacement. 37 …”
Section: Introductionmentioning
confidence: 99%